Sebuah Analisis Beban Kerja Untuk Menentukan Tenaga Kerja Yang Optimal Pada Karyawan di PT IJI - Yeni Lisaw Maha (Journal of Optimization System and Ergonomy Implementation, 2023)
PT IJI is a company that operates in the field of outsource facility services, trade, and technology, one of its projects is at Mall Kalibata City. During the course of the project there were some problems such as the monthly activity plan (RKB) that had been drawn up by the team was not implemented according to the schedule. This is because of the shortage of labor and the workload received by the workers on this project is excessive. Thus, the measurement of the workload as the basis for determining the optimum workforce needs should be done. In this study, using the Modified Full Time Equivalent (MFTE) method to identify the amount of workload received by the worker and determine the optimum workforce. The results of the calculation of the MFTE method, the whole worker as the object of this study had overload with an average value of MFTE of 2.27 (overload) and was given a proposal with an addition of the workforce of 15 people and the size of the value MFTE after the proposal of the improvement of the average workload to 1.14 (fit).